The effects of hydrogen on dynamic fracture toughness of high-strength low-carbon medium manganese steel. (April 2023) - Du, Y.; Gao, X.H.; Wang, X.N.; Dong, Y.; Zhang, B.; Wu, H.Y.; Sun, C.; Du, L.X.
Highlights: The effect of hydrogen on the dynamic fracture toughness of medium manganese steel was studied. The influence of retained austenite and martensite matrix on dynamic fracture toughness was studied. The newly formed martensite inherits the high hydrogen concentration of RA can decrease the fracture toughness for ductile fracture specimens. The HELP mechanism plays a dominant role in the ductile zone, and the HEDE mechanism plays a dominant role in the brittle zone under rapid loading. Abstract: The effect of retained austenite (RA) stability and dislocation density of martensite matrix on low-temperature dynamic fracture toughness and the hydrogen embrittlement (HE) susceptibility was investigated in a high-strength low-carbon medium manganese steel subjected to three different heat treatments, i.e., the inter-critical annealing at 630 °C (QHA), inter-critical annealing at 610 °C (QLA), and direct quenching (DQ). Dynamic cracked three-point bending tests were performed at 20 °C and −40 °C with and without hydrogen charging. The RA volume fraction and the martensite matrix's dislocation density significantly affected the dynamic fracture toughness and HE behavior. All QHA and QLA tested at 20 °C fractured in the ductile mode, but all DQ and QLA tested at −40 °C fractured in the brittle mode. Dynamic fracture toughness decreases with RA volume fraction under the same tested temperature. The HE mechanism in the ductile region is HELP, and that in the brittle region is HEDE.